A method for delivering lipophilic nutrients from red palm olein - Voon, Phooi Tee; Mat Sahri, Miskandar; Lim, Wei Huei; Lai, Oi Ming; Tan, Chin Ping; Lai, Wee Ting (2013)
A method for producing an organoleptic acceptable and quality stable product to act as delivery system of lipophilic nutriens from red palm olein is provided as a preferred embodiment of the present invention. Microcapsules comprised of red palm olein are prepared by preparing oil in water emulsion and subsequently dried with a flow of heat. The microcapsules are in the form of a solid state delivery system. The Moisture content of the product is less than 10%. Once dried, the product can be packaged and stored at room temperature for long periods of time.